2021
DOI: 10.1016/j.lungcan.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses identified ion channel genes GJB2 and SCNN1B as prognostic biomarkers and therapeutic targets for lung adenocarcinoma

Abstract: Integrative analyses identified ion channel genes GJB2 and SCNN1B as prognostic biomarkers and therapeutic targets for lung adenocarcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The expression levels of CCNA2, CDC25C, ERO1A, CDK1, PLK1, ITGB4, and GJB2 could influence the cancer progression [21][22][23][24][25][26]. For instance, ERO1A, also known as ERO1L, promotes IL6R secretion by targeting disulfide bond formation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of CCNA2, CDC25C, ERO1A, CDK1, PLK1, ITGB4, and GJB2 could influence the cancer progression [21][22][23][24][25][26]. For instance, ERO1A, also known as ERO1L, promotes IL6R secretion by targeting disulfide bond formation.…”
Section: Discussionmentioning
confidence: 99%
“…The study also identified 22 unique ion channels in the metastatic state, of which GRIK2, GJB3, KCNB2, KCNA1 and KCNK2 were previously reported in breast cancer metas-tasis [67][68][69][70][71]. Similarly, GABRG1, KCNQ3, GABRB2, GRIN2A, GRIA4, P2RX6, CACNA2D1, SCNN1G and TRPC4 were previously reported in metastasis in various other tumors [72][73][74][75][76][77][78][79][80][81][82][83]. TRPV3, GABRG3, KCNT1, GJA5, KCNN1, GRIK5, CLCNKB and CHRNB2 were identified as putative ion channels that might play a crucial role in breast cancer metastasis.…”
mentioning
confidence: 75%
“…It has been shown that GJB2 is an independent prognostic biomarker for LUAD, and patients with GJB2 overexpression have shorter overall survival. GJB2 may also be a potential prognostic factor for KIRC, as shown by pan-cancer analysis ( 22 ).…”
Section: Discussionmentioning
confidence: 99%